Translator learners' strategies in local and textual metaphors - Gebbia, Chiara Astrid (Frontiers in Communication, 2023)
Metaphor is more than understanding and expressing an abstract concept in terms of a concrete one (Lakoff and Johnson, 1980). Pre-linguistically, it is the conceptual creativity that resides in the entities yet to be expressed. Linguistically, it is the invention that expands the boundaries of words. Contextually, it is the preservation or generation of polysemy that brings about a confrontation of meanings (Prandi, 2017). As such, metaphor is also a universal creative mechanism of semantic innovation and an artful discourse feature (Ricoeur, 1973). Both Metaphor and Translation Studies, however, have mostly addressed conventional metaphors and professional translators, thereby neglecting students’ behaviors when translating creative metaphors, especially at discourse level. The main objective of this task-based descriptive study is therefore to investigate to what extent and how the translation strategies spontaneously adopted by 73 translator students are influenced by local, creative metaphors and by their textual patterning. The analysis of the data showed that while isolated, non-conflictual metaphors did not pose any challenges, the diverse patterns of conflictual ones hampered the translation outcome. At the micro-level, literal and explicitation strategies result in neutral, less connotative renditions. When omission prevails in correlation to metaphor clusters, the target texts appear more condensed, overtly informative, and lack the metaphorical diversity and cohesion of the source ones. As a result, the appealing linguistic jocularity deriving from exploiting metaphors and puns is toned down. Since students tend to avoid creative solutions, these findings will serve as a preliminary discussion on how students’ strategic and textual competence can benefit from cognitive-informed, conflict-based (Rizzato, 2021) inferencing skills by exploiting the metalinguistic nature of creative metaphors and puns.